Retrieval of the gastric specimen following laparoscopic sleeve gastrectomy. Experience on 275 cases. (April 2016) - Maietta, P.; Milone, M.; Coretti, G.; Galloro, G.; Conzo, G.; Docimo, G.; Ruggiero, R.; Musella, M.
Abstract: Severe obesity leads to a high incidence of complications and a decrease in life expectancy, especially among younger adults. Laparoscopic sleeve gastrectomy (LSG) first intended as the first step of biliopancreatic diversion with duodenal switch is gaining a per-se procedure role because of its effectiveness on weight loss and comorbidity resolution. Different techniques have been described for specimen extraction in LSG. In this article we report the technique adopted in 275 LSGs performed in our department. In the first 120 LSGs performed from 2007, the specimen was extracted through a mini laparotomy. In the following 155 cases the technique has been simplified: the grasped specimen has been withdrawn through the 15 mm trocar site. We registered in the fist group six cases of wound infection (5%), ten cases of hematoma (8.3%) and four cases of port site hernia (3.3%). In the second group only one case of hematoma (0.6%, p = 0.01) but no cases of wound infection (p = 0.01) or port site hernia, (p = 0.03) although we registered a specimen perforation during retrieval in 16 patients, were reported. The technique described in the 155 cases of the control group has shown to be more effective than the technique we used in the case group, allowing significantly lower operative time (112.9 ± 1.0 vs 74.9 ± 9.1 p < 0.001) and complications, and providing unchanged costs.